2022
DOI: 10.1063/5.0086912
|View full text |Cite
|
Sign up to set email alerts
|

Red InGaN micro-light-emitting diodes (>620 nm) with a peak external quantum efficiency of 4.5% using an epitaxial tunnel junction contact

Abstract: We present efficient red InGaN 60 × 60 μm2 micro-light-emitting diodes ( μLEDs) with an epitaxial tunnel junction (TJ) contact. The TJ was grown by metal-organic chemical vapor deposition using selective area growth. The red TJ μLEDs show a uniform electroluminescence. At a low current density of 1 A/cm2, the emission peak wavelength is 623 nm with a full-width half maximum of 47 nm. The peak external quantum efficiency (EQE) measured in an integrating sphere is as high as 4.5%. These results suggest a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…4(b). 16,18,20,21,23,26,33,[37][38][39][40][41] We also calculated the EQEs and WPEs of the LEDs at various injection currents, as shown in Fig. 5.…”
Section: (B) the Fwhm Emission Of The Leds Is Comparable To State-of-...mentioning
confidence: 99%
“…4(b). 16,18,20,21,23,26,33,[37][38][39][40][41] We also calculated the EQEs and WPEs of the LEDs at various injection currents, as shown in Fig. 5.…”
Section: (B) the Fwhm Emission Of The Leds Is Comparable To State-of-...mentioning
confidence: 99%
“…It is noted that the peak EQE of 6% is the highest one reported among the InGaN-based red μLEDs. 17,[19][20][21][22][23][24][25][26]29,30 The EQE of the InGaN μLEDs maintains as high as 4.5% at 100 A/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Fewer damage sidewalls etching process is a good approach to improve the efficiency of ultra-small InGaN red µLEDs. More recently, Li et al from UCSB reported 623 nm red InGaN µLEDs (60 × 60 µm 2 ) with a peak EQE of 4.5% using epitaxial tunnel junction (TJ) contact [27]. GaN TJ offers a better current spreading and less optical loss, which can improve efficiency.…”
Section: Robust Temperature Property Of Ingan Red µLedsmentioning
confidence: 99%